The Development of Musical Talent in Different Life Periods: A Case Study - Tjaša Drovenik Adamec, Drovenik Adamec; Kovačič, Bojan (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
Through a case study of the internationally renowned organist, Tea Kulaš, we aim to investigate the influence of 29 factors on the development of musical talent at different stages of life, from early childhood to early adulthood (i.e., 3–35 years of age). The results show that in childhood and earlier stages of life, the development of musical talent is significantly influenced by external factors, while the importance of the influence shifts to internal factors in later stages of life.